Identification of male COPD patients with exertional hypoxemia who may benefit from long-term oxygen therapy. - Brian J Garnet; Elie Jean; Rodrigo Diaz Lankenau; Michael A Campos (PLoS ONE, 2023)
Several studies have documented increased exercise capacity with supplemental oxygen therapy in patients with COPD and exertional hypoxemia, but a large trial failed to demonstrate a survival benefit in this population. Due to the heterogeneity observed in therapeutic responses, we sought to retrospectively evaluate survival in male COPD patients with exertional hypoxemia who had a clinically meaningful improvement in exercise capacity while using supplemental oxygen compared to their 6-minute walk test distance (6MWD) while walking on room air. We defined them as responders or non-responders based on a change in 6MWD of greater or less than 54m. We compared their clinical and physiologic characteristics, and their survival over time. From 817 COPD subjects who underwent an assessment for home oxygen during the study period, 140 met inclusion criteria, with 70 (50%) qualifying as responders. There were no significant differences in demographics, lung function, or baseline oxygenation between the groups. The only difference noted was in the baseline 6MWD on room air, with responders to oxygen therapy having significantly lower values (137 ± 74m, 27 ± 15% predicted) compared to non-responders (244 ± 108, 49 ± 23% predicted). Despite their poorer functional capacity, mortality was significantly lower in responders after adjusting for age, comorbidities, and FEV1 (HR 0.51; CI 0.31-0.83; p = 0.007) compared to non-responders after a median follow-up time of 3 years. We conclude that assessing the immediate effects of oxygen on exercise capacity may be an important way to identify individuals with exertional hypoxemia who may benefit in the long-term from ambulatory oxygen. Prospective long-term studies in this subset of patients with exercise induced hypoxemia are warranted.